Efficiency of new local method of treatment and prevention of inflammatory diseases of oral mucous membrane and parodontium in smokers - S. A. Schneider; L. S. Kravchenko; J. F. Burdina; N. S. Fizor; S. V. Scherbakov (Kazimierz Wielki University, 2017)
Treatment and prevention of inflammatory diseases of oral mucous membrane and parodontium at smokers is one of the most difficult problem in stomatology today. Purpose of research: estimation of clinical efficiency of local application of developed agent for oral cavity care apigel at treatment and prevention of inflammatory diseases of oral mucose membrane and parodontium at smokers. Local application of the new apigel based on propolis in the complex medical treatment of smokers patients favourably affects the clinical symptoms of inflammation in the oral mucous membrane and parodontium. As compared with patients who had traditional anti-inflammation therapy with the local use to the stomatologyc gel with chamomile, the patients treated with local application of new apigel had decline of the bleeding gums. The occurred more rapid improvement of inflammation painfulness, which correlated with the improvement of hygienic state of oral cavity and promoted to prevention of bacterial content of damaged mucous surfaces. Estimation of microvasculatory blood stream by the method of ultrasonic Doppler flowmetry revealed more rapid normalization of volume and linear high systole, speed of blood stream in the parodontal tissues in case of use of new local method that testified to the less pronounced inflammation of oral mucosa. The effect of the developed local agent in smokers patients with inflammatory diseases of oral mucose membrane and parodontium at smokers creates the best conditions for removal of violations of oral cavity microbiocenosis and restores structural-functional state of parodontium and oral mucosa. The authors came to conclusion that local application of the offered method of medical treatment reduces terms of renewal of structural-functional integrity of oral mucosa, helps in preventing development of inflammatory complication, improves the hygienic state of oral cavity, renders the regenerative action on oral mucosa tissues, which improves efficiency of medical treatment and quality of life of smokers patients.